The Role of Institutional Ownership and Audit Quality in Moderating the Effect of Free Cash Flow on Earnings Management - Arafah, Muhammad; Arfan, Muhammad; Zuraida (International Journal Labs, 2025)
This study aims to examine the effect of institutional ownership and audit quality in moderating the relationship between free cash flow and earnings management of non-financial firms in Indonesia. This study uses 179 observations for the year 2019-2023 of non-financial companies listed in the Indonesia Stock Exchange and sampling technique used is proportionate stratified random sampling. Then, data are analyzed using multiple linear regression analysis and moderated regression analysis (MRA). The study's findings suggest that free cash flow has positive effect on earnings management. It has been demonstrated that audit quality plays a role in reducing or mitigating the positive influence of free cash flow on earnings management. However, on the other hand, institutional ownership does not play a role in moderating the effect of free cash flow on earnings management. Unless audited by a reputable public accounting firm, investors and prospective investors should be cautious in funding businesses with significant free cash flow since it may encourage managers to engage in earnings management. If financial statements of a company are audited by a reputable public accounting firm, the manager’s motivation to engage in earnings management may be reduced. In order to explain how free cash flow affects earnings management, this study adopts a novel strategy by combining audit quality and institutional ownership characteristics as moderating variables.